Analysis of Financial Performance at PT Bank Central Asia Tbk (BCA) for the 2020-2022 Period Using Liquidity Ratios - Rufus Tanaka; Muhammad Ali; Mursalim Nohong (Paulus Journal of Accounting (PJA), 2023)
Financial Performance Analysis at PT Bank Central Asia Tbk (BCA) uses Liquidity Ratios. This article reviews the financial performance of PT Bank Central Asia Tbk (BCA) for the 2020-2022 period using liquidity ratio analysis. This research method is a descriptive research method, namely explaining the performance assessment at BCA using liquidity ratio analysis, which includes the current ratio, quick ratio and cash ratio. The results of this research show that the liquidity ratio in the calculation of the current ratio, quick ratio and cash ratio experiences fluctuating movements. In terms of current ratio, in 2020 it was at 158%, which then decreased in 2021 and increased in 2022. In terms of quick ratio, in 2020 it was at 149%, which then decreased in 2021 and increased in 2022. In terms of cash ratio, in 2020 it was at 129%, which then decreased in 2021 and increased in 2022.